The Reef-fish Fauna of the Northern Patagonian Gulfs, Argentina, South-western Atlantic - Galvan, David Edgardo (2009)
A checklist containing 29 species of reef fishes recorded at the gulfs San José and Nuevo in Argentina (42°-43°S) is provided. The reef-fish assemblages of the San José and Nuevo gulfs are a mix of warm-temperate fauna from the South-western Atlantic Province, and cold-temperate species from the South-American Province; however, warm-temperate fishes dominated in both gulfs. The presence of the families Bovichtidae, Eleginopidae, Nototheniidae, Congiopodidae, Sebastidae and Moridae distinguished the Patagonian region from the rest of the Atlantic coast.